Walter Scott and Short Fiction - Cook, Daniel (Edinburgh University Press, 2022)
A study of Walter Scott's short stories, novella and talesProvides an extensive study of seventeen works of short fiction by one of Scotland's most influential writers of all timePlaces Scott's shorter fiction within different generic contexts and outlines the extraordinary reach and range of the short story in nineteenth-century Scotland and beyondChallenges recent surveys of the history of the short story, which either place Scott at the origin (but largely ignore his works) or ignore him completelyComplements Edinburgh University Press's extensive catalogue of Walter Scott studies, including the Edinburgh Edition of the Waverley NovelsThis book is the first extensive study of seventeen works of short fiction by one of Scotland's most influential writers of all time. It examines the author's only collection of short stories, Chronicles of the Canongate, periodical and gift-book pieces, and interpolated tales that appeared in the novels.Through careful readings of, amongst others, the Highland stories ('The Highland Widow' and 'The Two Drovers'), his Indian novella (The Surgeon's Daughter), Gothic keepsakes ('My Aunt Margaret's Mirror' and 'The Tapestried Chamber'), and his Calabrian tale Bizarro, this book offers new insights into the production and consumption of short stories, novellas, tales, sketches and other forms of fiction in the early nineteenth century and beyond